(untitled) (Research, Society and Development, 2020)
The Spodoptera cosmioides pod caterpillar has been causing serious damage to crop of economic interest in Brazil, especially soybean (Glycine max), demanding the need to find a sustainable and efficient way to manage this pest. The present work evaluated the efficiency of applied biological control and chemical control in the management of S. cosmioides in soybean culture under field conditions. The experimental design used was randomized blocks (DBC), composed of five treatments, four blocks and three applications. Bacillus thuringiensis (Bt) was tested at 200 mL ha-1, Metarhizium rileyi isolated UFMS 03 at 2.0 Kg ha-1, Baculovirus at 200mL ha-1, Diamide Anthranilica at 50mL ha-1 and the control (without product application ), being mixed with adhesive spreader (Tween 80® 0.01%). The number of live caterpillars was evaluated, as well as the efficiency of the tested products through the reduction of the insect pest population, in addition to phytotechnical parameters. The bioinsecticide based on B. thuringiensis was the most efficient in controlling S. cosmioides, providing better phytotechnical parameters. The estimated total productivity showed statistically superior results for biological treatments, except for treatment with Baculovirus.